Measuring the quality of management in education. Review article - Crissien-Borrero, Tito-José (El Profesional de la información, 2019)
The objective of this study is to perform a review and contextualize the existing definitions of educational quality from the managerial point of view. We will be presenting also the factors that have been considered to support managerial decision making within educational institutions. Relevant research related to the different models for measuring educational quality and the different factors that affect this quality are discussed. The existing methodological gap of the statistical processes, the theoretical evidences and the number of investigations in every level of education are identified. The results provide a framework for future research and can become the basis for the design and construction of multidimensional models for educational management quality measurement needs of educational institutions. The results evidence also the lack of a single criterion to build the indicators, as well as the fact that there is a strong of subjectivity in the measuring processes.